DDEL-04. Pharmacokinetic/Pharmacodynamic analysis of the DNA methyltransferase inhibitor 5-azacytidine shows adequate brain tissue penetration with intravenous administration in a DIPG mouse patient-derived xenograft model. (3rd June 2022) - Groves, Andrew; Jones, Kristen; Cameron, Amy; Panditharatna, Eshini; Morrow, Murry; Mozarsky, Brett; McCully, Cynthia; Peer, Cody; De Nguyen, Quang-; Filbin, Mariella; Warren, Katherine
Abstract: One of the biggest obstacles in developing effective therapies for CNS tumors is drug delivery due to the enigmatic challenge of penetrating the blood-brain barrier. 5-azacytidine is a DNA methyltransferase inhibitor which was the first epigenetic targeting chemotherapeutic approved by the FDA. Altered DNA methylation is a hallmark of many cancers, including diffuse intrinsic pontine glioma (DIPG). 5-azacytidine has been shown to be active in DIPG cell lines, with only modest in-vivo activity. We have previously shown in a non-human primate model that intravenous (IV) administration of 5-azacitidine does not result in measurable CSF penetration, while intrathecal (IT) administration does and is well tolerated. To follow up these studies in a tumor-bearing mouse model (HSJD DIPG007), we performed pharmacokinetic (PK) and pharmacodynamic (PD) analysis following IV vs. IT administration. Forty mice were randomized to receive four weekly doses of IV 5-azacytidine (25 mg/kg), IT 5-azacytidine (40 μg), or corresponding vehicle controls. Four mice from each arm were sacrificed 30 minutes after the last dose and brain tissue was collected for PK/PD analysis. Drug concentration was quantified using ultra-high-performance liquid chromatography with tandem mass spectrometric detection, while pharmacodynamic methylation profiling was performed using the Infinium MethylationEPIC BeadChip (850K). Brain tissue concentrations were comparable between IV (7.6-58.0 pg/mg) and IT (6.9-63.9 pg/mg) dosing. Methylation profiling unexpectedly showed a significantly more pronounced pharmacodynamic effect with IV dosing vs. IT, with a mean decrease of 13.6% vs. 2.6% in global DNA methylation score (GDMS = percentage of highly methylated (beta ≥ 0.7) genomic loci) compared to vehicle controls. For the remaining mice, there was no significant difference in survival. Our results are encouraging that phenotypically relevant demethylating effects can be achieved in the CNS with IV 5-azacytidine administration; however, further research is needed to develop promising combination strategies in DIPG.